ENVIRONMENTAL FRAGILITY OF THE IRAÍ RIVER BASIN – WATER SUPPLY SOURCE FOR CURITIBA, PARANÁ - Marcon, Amanda Köche; Lingnau, Christel; Galvão, Franklin (Floresta, 2021)
This research aimed to compare two methods of determining the environmental fragility of a vital source in the region of Curitiba, Paraná, the Iraí river basin. The determination of the environmental fragility was carried out based on the integration of geological, pedological, geomorphological characteristics and land use, using the emergent fragility and Natural Vulnerability to Soil Loss methods. Most of the Iraí River basin was classified as weak to intermediate environmental fragility by both methods. The methods showed equal fragility ratings in 74% of the basin area. The greatest fragilities were found in areas with recent sedimentation, soils with high instability, slopes higher than 12% and land use areas with low protective potential. The emergent fragility method highlighted the effect of land use, accentuating the fragility of the most vulnerable classes. In contrast, the Natural Vulnerability to Soil Loss method attenuated this land-use effect, softening the vulnerability. The fragility maps indicated that different results might be obtained, especially on the threshold between fragility classes and polygons where land-use makes the environment more vulnerable. Thus, the method selection for determining environmental fragility depends on the relevance necessary for land-use. The emergent fragility method is advantageous for showing the fragility in areas mainly occupied by classes of land use of high vulnerability.